Developments in delivery of medications for inner ear disease. (May 2013) - Staecker, Hinrich; Rodgers, Brian
<x xml:space="preserve">Abstract</x> Introduction: Hearing loss, tinnitus and balance disturbance represent common diseases that have tremendous impact on quality of life. Despite the high incidence of inner ear disease in the general population, there are currently no dedicated pharmacologic interventions available to treat these problems. Areas covered: This review will focus on how treatment of inner ear disease is moving toward local delivery at the end organ level. The authors will discuss current practice, ongoing clinical trials and potential areas of development such as hair cell regeneration and neurotrophin therapy. Expert opinion: The inner ear is accessible through the middle ear via the oval and round windows allowing diffusion of drugs into the perilymph. With a better understanding of the physiology of the inner ear and the underlying molecular causes of inner ear disease there is great potential for the development of novel therapeutics that can be locally administered. At present, there is a rapid development of drugs to target diverse inner ear diseases that cause sensorineural hearing loss and balance dysfunction.